2017
DOI: 10.1007/s00380-017-0955-x
|View full text |Cite
|
Sign up to set email alerts
|

Conditional knockout of activin like kinase-1 (ALK-1) leads to heart failure without maladaptive remodeling

Abstract: Activin like kinase-1 (ALK-1) mediates signaling via the transforming growth factor beta (TGFβ) family of ligands. ALK-1 activity promotes endothelial proliferation and migration. Reduced ALK-1 activity is associated with arteriovenous malformations. No studies have examined the effect of global ALK-1 deletion on indices of cardiac remodeling. We hypothesized that reduced levels of ALK-1 promote maladaptive cardiac remodeling. Methods We studied ALK-1 conditional knockout mice (cKO) harboring the ROSA26-CreER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…No phenotypic affect was observed with cardiomyocyte specific deletion of Alk1 . Recently we demonstrated that global inducible knockout of Alk1 expression in adult mice led to the development of gastrointestinal arteriovenous malformations and high output HF without structural or signaling changes consistent with pathological cardiac remodeling [8, 9]. We have now studied Alk1 haploinsufficient mice and observed no change in cardiac structure or function at baseline compared to WT mice; however cardiac function worsened and cardiac fibrosis increased in Alk1 +/− mice after TAC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No phenotypic affect was observed with cardiomyocyte specific deletion of Alk1 . Recently we demonstrated that global inducible knockout of Alk1 expression in adult mice led to the development of gastrointestinal arteriovenous malformations and high output HF without structural or signaling changes consistent with pathological cardiac remodeling [8, 9]. We have now studied Alk1 haploinsufficient mice and observed no change in cardiac structure or function at baseline compared to WT mice; however cardiac function worsened and cardiac fibrosis increased in Alk1 +/− mice after TAC.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several reports have implicated a role for ALK1 as a negative regulator of fibrosis in vascular tissue, cartilage, the liver and the kidney [9, 1619]. From these observations, we hypothesized that reduced ALK1 activity promotes cardiac fibrosis in HF by limiting SMAD1 activation.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Tissue-specific deletion demonstrates a requirement for acvrl1 in ECs [56, 57]. Conditional global or endothelial-specific Acvrl1 deletion is also lethal in neonates and adults, with animals exhibiting AVMs and hemorrhage in uterus, lung, gastrointestinal tract, and retina, but not in brain or skin [5762]. Interestingly, brain and skin AVMs develop in Acvrl1 -deleted mice in response to VEGF stimulation or wounding, suggesting that a “second hit” that triggers angiogenesis is required for AVM development in these tissues [5659, 6366].…”
Section: Animal Models Of Hhtmentioning
confidence: 99%
“…Interestingly, brain and skin AVMs develop in Acvrl1 -deleted mice in response to VEGF stimulation or wounding, suggesting that a “second hit” that triggers angiogenesis is required for AVM development in these tissues [5659, 6366]. Global deletion in adulthood is also associated with cardiomegaly and high-output heart failure [57, 62] that may be caused, as in HHT patients, by low peripheral vascular resistance. Together, these studies point to a critical requirement for Acvrl1 in vascular development and maintenance throughout life.…”
Section: Animal Models Of Hhtmentioning
confidence: 99%